Soil conditioning effects of Phragmites australis on native wetland plant seedling survival - Crocker, Ellen V.; Nelson, Eric B.; Blossey, Bernd (Ecology and evolution, 2017)
Interactions between introduced plants and soils they colonize are central to invasive species success in many systems. Belowground biotic and abiotic changes can influence the success of introduced species as well as their native competitors. All plants alter soil properties after colonization but, in the case of many invasive plant species, it is unclear whether the strength and direction of these soil conditioning effects are due to plant traits, plant origin, or local population characteristics and site conditions in the invaded range. Phragmites australis in North America exists as a mix of populations of different evolutionary origin. Populations of endemic native Phragmites australis americanus are declining, while introduced European populations are important wetland invaders. We assessed soil conditioning effects of native and non‐native P. australis populations on early and late seedling survival of native and introduced wetland plants. We further used a soil biocide treatment to assess the role of soil fungi on seedling survival. Survival of seedlings in soils colonized by P. australis was either unaffected or negatively affected; no species showed improved survival in P. australis‐conditioned soils. Population of P. australis was a significant factor explaining the response of seedlings, but origin (native or non‐native) was not a significant factor. Synthesis: Our results highlight the importance of phylogenetic control when assessing impacts of invasive species to avoid conflating general plant traits with mechanisms of invasive success. Both native (noninvasive) and non‐native (invasive) P. australis populations reduced seedling survival of competing plant species. Because soil legacy effects of native and non‐native P. australis are similar, this study suggests that the close phylogenetic relationship between the two populations, and not the invasive status of introduced P. australis, is more relevant to their soil‐mediated impact on other plant species. Organismal photograph of Phragmites australis (EU). Photograph shows assessment of seedlings transplanted into EU patches.